Microbial decolorization of triazo dye, direct blue 71 by mixed bacterial culture isolated from Malaysian soil - Mohd Zin, Khairunnisa' (2020)
Polluted wastewater from textile dyeing industrial sectors has causes severe effect towards human, plant and marine creatures and the treatment process is truly challenging. In this study, a mixed bacterial culture was isolated from Malaysian soil, screened and identified to successfully decolorize Triazo-bond Direct Blue 71 dye and act as the sole source of carbon and nitrogen. The free cells were also immobilized for better decolorization at higher concentration of dye by using sodium alginate. Response surface methodology (RSM) and Artificial Neural Network (ANN) were used to optimize the decolorization efficiency for both free and immobilized cells. Significant effect on DB71 dye decolorization percentage by free cells is denoted by the experimental variables of dye concentration, yeast extract, and pH. The optimum conditions for dye decolorization by immobilized mixed culture were determined by four variables which were dye concentration, alginate concentration, number of beads and beads size. GCMS and FTIR analysis were used to characterize the metabolites after the decolorization. Other than that, kinetics modelling study of DB71 dye decolorization allowed the estimation of decolorization rate of free and immobilized cells. Major bacterial group found from the metagenomics analysis consist of Acinetobacter (30%), Comamonas (11%), Aeromonadaceae (10%), Pseudomonas (10%), Flavobacterium (8%), Porphyromonadaceae (6%), and Enterobacteriaceae (4%). Proteobacteria (78.61%), then Bacteroidetes (14.48%) and Firmicutes (3.08%) were among the richest phylum in the mixed bacterial culture. The optimum condition for free cells predicted by RSM is at 150 mg/L of dye concentration, 3 g/L of yeast extract and pH of 6.645. ANN predicted the optimum condition at 150 mg/L, 2.9 g/L of yeast extract and pH of 6.7. Higher prediction and accuracy in the fitness was found in ANN model as proved by R2 and AAD values of 0.99 and 0.04 subsequently fitness compared to the RSM. ANN model for immobilized cells offered a better prediction than RSM with R2 of 0.99. The ANN model predict the decolorization by immobilized cell is optimum at 200 mg/L, 0.966 % of alginate concentration, 50 number of beads and 0.599 cm of beads size. Moreover, the result from GCMS and FTIR analysis of the metabolites from the decolorization of dye shows that the reduction of dye caused the absence of the untreated sample and emergence of new peaks in the treated sample in FTIR spectrum. In addition, GCMS result from the treated sample shows no toxic secondary metabolites were formed. Luong model predicted the rate of decolorization by free cell at 10 %hr-1 by using the kinetic modelling and dye concentration at 159.5 mg/L completely inhibited the decolorization based on the Sm value. Aiba model predicted the rate of decolorization by immobilized cell is at 4.645 %hr-1. The use of mixed bacterial culture was found to be efficient for the decolorization of DB71 dye in this study. The optimization of immobilized cell by using RSM and ANN using sodium alginate resulted to better decolorization of dye at higher concentration which is up to 200 mg/L. Moreover, the effect of metal ions towards the decolorization shows that gel beads through immobilization were able to protect against toxic substance. It is reflected by a great tolerance result towards metal ions over free cells during DB71 dye decolorization where occurrence of metal ions may disrupt the decolorization process. The decolorization of Direct Blue 71 dye by immobilized cell was still higher than 90 % even with the presence of 1 mg/L of mercury, nickel, copper, lead, arsenic, chromium, cadmium and silver in the solution and slight decrease of decolorization was observed for both free and immobilized cell compared to the control samples. In conclusion, all the objectives of this study were achieved accordingly. Environmental pollution caused by the released of industrial effluent containing dye has been affecting the water quality in Malaysia. Biological practice using microorganisms provides a complete degradation with no secondary pollutant besides the cost effective advantage compared to the physical and chemical wastewater treatment. There are few reported works on azo dye decolorization by mixed bacterial culture without the aid of carbon and nitrogen source. Therefore, this study found and optimized a potent mixed bacterial culture that could degrade Direct Blue 71 dye in facultative anaerobic condition and no added carbon and nitrogen sources are needed to completely decolorize the dye with no introduction of secondary toxic metabolites based on the metabolites analysis result.